2022
DOI: 10.3389/fphar.2022.1019670
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids of Oldenlandia diffusa (Willd.) Roxb. suppresses the growth of hepatocellular carcinoma through endoplasmic reticulum stress-mediated autophagy and apoptosis

Abstract: Hepatocellular Carcinoma (HCC) is one of the most common malignant tumors in the world. Although the current treatment methods for HCC are gradually increasing, its efficacy still cannot meet the medical needs of patients with liver cancer, and new and effective treatment strategies are urgently needed. The total flavonoids of Oldenlandia diffusa (FOD) are the main active components in Oldenlandia diffusa, which have anti-inflammatory, antioxidant and anti-tumor effects, but their mechanism of action in liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Studies have revealed that endoplasmic reticulum stress can inhibit the expression of autophagy‐related genes, including ATG12 and ATG5, allowing liver cancer cells to evade autophagic degradation and enhance their capacity for growth and proliferation. Consequently, the role of autophagy in liver cancer cells is counteracted by endoplasmic reticulum stress 30 . In conclusion, the interplay between ER stress and cell autophagy plays a crucial role in the progression of liver cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have revealed that endoplasmic reticulum stress can inhibit the expression of autophagy‐related genes, including ATG12 and ATG5, allowing liver cancer cells to evade autophagic degradation and enhance their capacity for growth and proliferation. Consequently, the role of autophagy in liver cancer cells is counteracted by endoplasmic reticulum stress 30 . In conclusion, the interplay between ER stress and cell autophagy plays a crucial role in the progression of liver cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, the role of autophagy in liver cancer cells is counteracted by endoplasmic reticulum stress. 30 In conclusion, the interplay between ER stress and cell autophagy plays a crucial role in the progression of liver cancer. Hence, future investigation should focus on elucidating the underlying mechanisms of this interaction to pave the way for novel therapeutic strategies in liver cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that the alkaloid veratramine significantly inhibits the proliferation, migration, and invasion of HepG2 cells and induces autophagy-mediated cell death by inhibiting the PI3K/Akt/mTOR signaling pathway [ 96 ]. Both in vitro and in vivo studies have demonstrated that the main active component, total flavonoids of Hedyotis diffusa Willd, induces endoplasmic reticulum stress (ER stress) and activates the PERK/EIF2α/ATF4 signaling pathway, inducing apoptosis and activating autophagy in HCC cells [ 60 ].…”
Section: The Main Action Pathway and Potential Mechanism Of Natural C...mentioning
confidence: 99%